A simple model for breakup time prediction of water-heavy fuel oil emulsion droplets. (January 2021) - Fostiropoulos, Stavros; Strotos, George; Nikolopoulos, Nikolaos; Gavaises, Manolis
Highlights: The equations of the simple fitting model are based on physical principles (heat convection and bubble growth timescales). The model can perform fast predictions with minimum CPU resources for a wide range of operating conditions. Abstract: Immiscible heavy fuel-water (W/HFO) emulsion droplets inside combustion chambers are subjected to explosive boiling and fragmentation due to the different boiling point between the water and the surrounding host fuel. These processes, termed as either puffing or micro-explosion, are investigated with the aid of a CFD model that solves the Navier-Stokes and energy conservation equations alongside with three sets of VoF transport equations resolving the formed interfaces. The model is applied in 2-D axisymmetric configuration and it is valid up to the time instant of HFO droplet initiation of disintegration, referred to as breakup time. Model predictions are obtained for a wide range of pressure, temperature, water droplet surface depth and Weber number; these are then used to calibrate the parameters of a fitting model estimating the initiation breakup time of the W/HFO droplet emulsion with a single embedded water droplet. The model assumes that the breakup time can be split in two distinct temporal stages. The first one is defined by the time needed for the embedded water droplet to heat up and reach a predefined superheat temperature and a vapor bubble to form; while the succeeding stage accounts for the time period of vapor bubble growth, leading eventually to emulsion droplet break up. It is found that the fitting parameters are ±10% accurate in the examined range of We < 220, T < 2000 K, P < 140 bar and δ < 0.15.